An inter-ply friction model for thermoset based fibre metal laminate in a hot-pressing process. (15th December 2021) - Liu, Shichen; Sinke, Jos; Dransfeld, Clemens
Abstract: Forming process with pre-stacked and uncured thermoset fibre metal laminate offers improved deformability compared to full-cured laminate especially for the production of complex structural components. This work investigated the friction behaviour at the metal-prepreg interface of glass fibre reinforced aluminium laminate through an inter-ply friction test. The influence of sliding velocity, normal force, fibre orientation and resin viscosity coupled with temperature on static and kinetic friction coefficients were studied. The kinetic friction behavior in the transition region between mixed and hydrodynamic lubrication, showed a good agreement with the Stribeck-curve theory. While for the static friction, a modified Coulomb friction model was found to fit the experimental results. These models were translated into a phenomenological inter-ply friction model which was incorporated into Abaqus/Explicit as a user-defined friction subroutine for verification. The findings contribute to the development of the forming process with fibre metal laminates.